The Role of NGOs in Resolving the Syrian War: A Case Study of The Carter Center - Athilla Nadiyah (Center of Peace, Conflict and Democracy - Hasanuddin University, 2025)
This study examines the crucial role carried by the Carter Center in facilitating negotiations and resolving the Syrian war between 2016 and 2019. This time was characterized by severe humanitarian emergencies and intricate geopolitical factors. The Syrian civil war, known for its immense human suffering and widespread international participation, posed significant obstacles to peacebuilding endeavors. In the midst of this upheaval, the Carter Center emerged as a significant participant, utilizing its expertise in resolving conflicts to facilitate discussions and advance the cause of peace. This research utilizes a thorough examination of primary and secondary data, such as government reports, interviews with important individuals, and evaluations conducted in the field, to analyze the effectiveness of the Carter Center's actions. The research emphasizes the Center's comprehensive strategy, encompassing the facilitation of talks, support for ceasefire agreements, and promotion of humanitarian aid. This is done while upholding a position of neutrality and demonstrating a profound understanding of other cultures. The data demonstrate that the Carter Center played a crucial role in establishing avenues for communication and mitigating violence, despite the ongoing and changing obstacles. This thesis enhances our comprehension of the intricacies of international conflict resolution and highlights the crucial role that non-state actors may play in promoting peace by scrutinizing the Center's techniques and outcomes. The research highlights the significance of continuous, compassionate involvement in areas of conflict and provides valuable understanding of the wider consequences for international efforts to promote peace.